Eating Disorders: Distractions from Problems of Self and Meaning - Edwards, Emily (Trinity College Dublin, 2007)
This study focuses on how anorexia nervosa, compulsive overeating, as well as combinations of these disorders, are complex manifestations of emotional, psychological, and cultural difficulties. Emily's hypothesis is that some women implement eating disorders as a means of distracting themselves from existing problems in their lives, or from the meaninglessness of in general. Eating disorders are often perceived as coping mechanisms, or attempts to control life, but Emily seeks to validate the idea that some women go beyond these methods by escaping or avoiding difficult to deal with aspects of their lives by focusing primarily upon food and its avoidance.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: Eating Disorders; Gender Studies